Random Walks on the Stock Exchange of Singapore - HWANG, Soo Chiat (Institutional Knowledge at Singapore Management University, 1983)
Efficient security markets are well-known in developed countries and are a factor that foreign investors depend on. Information on the efficiency of security markets in less-developed countries is not as well-known. Analysis of the Singapore Stock Exchange reveals a 'weak form' of the hypothesis of efficiency based on the theory of random walks in share prices. The stock prices were tested for normality of the distribution of price changes. Though three of the individual share series showed departures from normality, overall the majority could be defined as normally distributed. Tests of independence were performed by serial correlation and non-parametric runs tests. Changes in share prices were deemed to be independent. Based on knowledge of developed countries' security markets, the market of Singapore is weakly efficient.